Conducta obstétrica en primigesta adolescente de 15 años de edad, 28 semanas de gestación con óbito fetal - Zambrano Chisaquinga, Jazmín Liseth (2021)
Stillbirth is one of the most difficult obstetric accidents to deal with. Both the pregnant woman and the fetus, despite complying with a purely physiological process such as pregnancy, are exposed to a series of risks that threaten their health and lives. Among the probable complications is intrauterine fetal death. (Vogelmann, Sánchez, & Sartori, 2008). For this reason, we present the case of a 15-year-old primiparous patient with a 28-week gestation pregnancy, who went to the Baba health center for prenatal control, referring to decreased fetal movements approximately 24 hours ago, reason for the which one decides to attend the consultation. The diagnostic methodology applied to the patient was immediate auscultation of heart beats that were absent, Leopold lieutenant maneuvers were applied as a result of the cephalic product with uterine height not according to gestational age. Taking into account that predisposing risk factors such as maternal age, first pregnancy, insufficient prenatal controls in number of 1 are added to this. The present case aims to raise awareness of the importance of prenatal controls, in order to be able to identify all possible risk factors that compromise maternal-fetal well-being.